Book Review: Experimental Archaeology: from Research to Society, by Isabel Cáceres et al - Patricia Machado (EXARC Journal, 2019)
“Experimental Archaeology: from Research to Society” is a transcript of the proceedings of the Vth International Congress of Experimental Archaeology in Tarragona, Spain, on the 25-27th October 2017. The conference, organized by Experimenta (Asociación Española de Arqueología Experimental), the Institut Català de Paleoecologia Humana i Evolució Social (IPHES), the Institut Català d’Arqueologia Clàssica (ICAC) and the Institut Català de Recerca en Patrimoni Cultural (ICRPC), should be considered within the scope of the programme of affirmation and development of the practices of experimental archaeology in Spain, a programme that consists of 12 years of activities. In fact (and as mentioned in the presentation) this initiative, that has now materialized in this book, attests to the “growing vitality of experimentation in Archeology” (Cáceres et al. 2018, 10) in Spain.